Friends matter: Ethnic-racial identity and school adjustment among African American and Latino early adolescents. Issue 4 (1st October 2020) - Medina, Michael A.; Rivas-Drake, Deborah; Jagers, Robert J.; Rowley, Stephanie J.
Abstract: The current study investigated the role of ethnic-racial identity (ERI) on early adolescents' school adjustment, as moderated by their school friends' aggregate ERI. The study drew data from a longitudinal socioemotional project in a Midwestern U.S. middle school. Surveys were administered twice over a 6-month interval with a sample of 161 African American and Latino sixth through eighth grade students. Results suggested a promotive role of ERI, as three dimensions (public regard, private regard, and resolution) were positively related to students' school adjustment. Additional results demonstrated the importance of friend group aggregate ERI; participants with high resolution or private regard, or a friend group with high aggregate resolution or private regard, reported higher levels of school adjustment than those with low individual and friend group-levels of these ERI dimensions. The findings provide insights into the role of social contexts and friend group beliefs on adolescents' ERI development and school experiences.